Coordinated Control Strategy of Electricity-Heat-Gas Integrated Energy System Considering Renewable Energy Uncertainty and Multi-Agent Mixed Game - Jing, Yan; Zhiqiang, Duan; Jiemai, Gao; Siyuan, Chen; Bing, Zhou; Yajie, Wang (Frontiers in Energy Research, 2022)
The Integrated Energy System (IES) can promote social energy transformation and low-carbon development, which is also an effective means to make contributions to energy structure optimization, energy consumption reduction, and new energy consumption. However, the IES has the characteristics of complex energy flow, and strong uncertainty with multi-agents. Therefore, traditional mathematical optimization models are difficult to comprehensively and accurately reflect the interest needs of different entities in the integrated energy microgrid. Aiming at this problem, a two-level collaborative control strategy model of “electricity-heat-gas” IES based on multi-agent deep reinforcement learning is proposed in this paper. The upper layer of this model is a multi-agent hybrid game decision-making model based on the Multi-Agent Deep Deterministic Policy Gradient algorithm (MADDPG), and the lower layer contains the power and gas flow calculation model. The lower model provides the upper model with the energy flow data of the IES and the upper layer rewards the decision-making behavior of the agent based on the energy flow data provided by the lower layer. Effectively solving the high-dimensional nonlinear optimization problem existing in the complex coupling network, this method can improve the convergence and training speed of the model. In this paper, the IEEE 33-node distribution network and 20-node gas network coupling system are provided to verify the model. The simulation results show that the proposed collaborative control strategy method can provide effective decision-making for electric-agent and gas-agent and realize the efficient and economic operation of the integrated energy system.